Budaya “Gamelan” sebagai Bahan Ajar Bahasa Indonesia bagi Penutur Asing dalam Mendukung Internasionalisasi Bahasa Indonesia - Leila Nur Ika Wati; Renda Adi Puspaningrum; Annisa Afrilia Widha Rukmana; Bulan Azzahra Puteri Barinto; Kundharu Saddhono (BADAN PENERBIT STIEPARI PRESS, 2024)
Gamelan is one of the cultural treasures in Indonesia. Through its various uniqueness, Gamelan becomes an interesting thing to learn. This study aims to describe Gamelan culture to be used as the main focus in the preparation of teaching materials for BIPA students. The method used in this study is qualitative research. This method is used to explore the use of Gamelan culture as Indonesian teaching material for foreign speakers. This approach allows researchers to thoroughly understand how the use of Gamelan can improve the understanding and mastery of Indonesian by non-native speakers. The object of this study is the use of Gamelan culture as a teaching material Indonesian for foreign speakers. The sources of data used in the research were from various books, scientific journal articles, and survey results regarding the needs of foreign speakers at Yale University regarding BIPA teaching materials. The subject of the study was BIPA teaching materials compiled as teaching media for foreign speakers at Yale University. The results showed that the teaching materials compiled in this study were in the form of prints arranged in book format. The material compiled in this teaching material is tailored to the needs of Indonesian for Foreign Speakers (BIPA) students, which can help BIPA students to master Indonesian easily. This teaching material contains the implementation of interactive and comprehensive learning.